Volatility transmission between the foreign exchange rate and stock market from 2004-2018: An empirical analysis of selected emerging markets of Asia-Pacific region - Adriano, Andrei Jose M. (Animo Repository, 2020)
Global financial integration and increasing trade facilitated the free movement of capital among countries, especially in financial markets. The complexities of the transactions and extremely large increase in the volume of transactions contributed to exposure to external shock by these markets. The paper used the BEKK-GARCH model to determine the direction of volatility spillover between the USD/KRW and USD/PHP foreign exchange markets and the stock markets of South Korea and the Philippines to better understand how financial shocks between markets can affect the stability and competitiveness of their markets and help regulators and policy makers correct these imbalances. The paper is broken down into four periods namely 2004 to 2013, 2004 to 2008, inclusive of the 2008 Global Financial Crisis, and from 2009 to 2013, and 2014 to 2018 for the two silent periods after the crisis. The results showed the South Korean markets had no evidence of shock transmissions but having bidirectional volatility transmission in the period of 2004 to 2008, and unidirectional volatility transmission from their stock market to their USD/KRW foreign exchange market for the rest of the other three time periods. This only proves that there is an interdependence and market integration between the foreign exchange market and stock market that may change from one period to another, especially during a financial crisis. This may trigger policy changes by the regulators in the aforementioned markets through adjustments that will be made either in the stock prices or foreign exchange rates to protect the competitiveness of these markets. Furthermore, it will help guide investors by providing them with early warning signs related to external shocks that can adversely affect their investments by employing portfolio asset allocation and risk management tools to protect their investments.